DDoS attacks on the rise and being used to mask other, more significant breaches. (September 2015) - Unknown
Abstract : There has been a sharp rise in the number of Distributed Denial of Service (DDoS) attacks and we're seeing a larger proportion of massive 'mega-attacks'. And DDoS is increasingly being used not to take down sites, but to mask other forms of hacking.